Visual outcome of Systemic Corticosteroid Treatment in Non-Arteritic Anterior Ischemic Optic Neuropathy (Journal of National Institute of Ophthalmology, 2026)
Purpose: To evaluate the visual outcome of patient with NAION treated with systemic corticosteroid. Methods: This non-randomized controlled clinical trial was conducted over 78 recently diagnosed patients with NAION (fewer than 14 days) in the Neuro-Ophthalmology Department of the National Institute of Ophthalmology and Hospital in Dhaka. The selection of patients was based on precise criteria for inclusion. Patients were allocated into two groups. In the A group, patients were treated with oral corticosteroid (prednisolone), with a starting average dosage of 1mg/kg of body weight daily for two weeks. After this time, the medication was tapered as 10 mg every five days for the next ten days, then 5 mg reduction every five days until it was stopped, tab. ecosprin, cap. Omeprazole and vitamin B complex. In the B group, patients were treated with tab. ecosprin, cap. omeprazole and vitamin B complex only. Best corrected visual acuity (BCVA) were measures at baseline, one month, three months and six months. Results: In the A group and B group, the patient's mean ages were 53.5 +/- 6.3 and 54.7 +/- 6.4 years, respectively. In the A group, 22 (57.9) were male while in the B group, 20 (50.0%) were male. In the A group, at baseline, the mean BCVA was 0.77±0.19 while in the B group, the mean BCVA was 0.75±0.13 (p=0.355). At 6th month, in the A group, the mean BCVA became 0.62±0.20 while in the B group, the mean BCVA was 0.65±0.21 (p=0.446). In relation to BCVA, the groups did not exhibit a difference of statistical significance at any time point as p>0.05. The majority of patients 50 (64.1%) remained static while 19 (24.4%) patients improved and 9 (11.5%) patients deteriorated. In relation to the final outcome, groups did not exhibit a difference of statistical significance. Conclusion: Oral corticosteroid does not have any additional benefit on visual outcome in patients with NAION. Additional randomized controlled trial are required to determine the efficacy of corticosteroid for the treatment of NAION.J.Natl.Inst.Ophthalmol.2024;7(2): 66-70